2006
DOI: 10.1073/pnas.0510050103
|View full text |Cite
|
Sign up to set email alerts
|

STIM1 has a plasma membrane role in the activation of store-operated Ca 2+ channels

Abstract: Receptor-induced Ca 2؉ signals are key to the function of all cells and involve release of Ca 2؉ from endoplasmic reticulum (ER) stores, triggering Ca 2؉ entry through plasma membrane (PM) ''storeoperated channels'' (SOCs). The identity of SOCs and their coupling to store depletion remain molecular and mechanistic mysteries. The single transmembrane-spanning Ca 2؉ -binding protein, STIM1, is necessary in this coupling process and is proposed to function as an ER Ca 2؉ sensor to provide the trigger for SOC acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
289
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 291 publications
(317 citation statements)
references
References 32 publications
26
289
1
1
Order By: Relevance
“…The luminal/extracellular N terminus contains a helix-rich sterile ␣-motif in addition to an EF-hand Ca 2ϩ sensor (6,18). The cytoplasmic C terminus contains two prominent coiled-coil regions followed by a flexible proline-rich domain (6,18). Based on the protein structure and several studies on STIM1, we hypothesize that two distinct types of interactions are likely important in the function of STIM1.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…The luminal/extracellular N terminus contains a helix-rich sterile ␣-motif in addition to an EF-hand Ca 2ϩ sensor (6,18). The cytoplasmic C terminus contains two prominent coiled-coil regions followed by a flexible proline-rich domain (6,18). Based on the protein structure and several studies on STIM1, we hypothesize that two distinct types of interactions are likely important in the function of STIM1.…”
mentioning
confidence: 95%
“…Although STIM1 resides predominantly in the ER and the plasma membrane (PM) (11), Orai1 is almost exclusively expressed in the PM (12). STIM1 functions as the Ca 2ϩ sensor in the ER that triggers the CRAC channel activation (5,6,11). However, its translocation to the PM upon activation (11,13) and functional role in the PM have also been demonstrated (6,14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A similar conclusion was independently reached by others [15][16][17][18], who in addition showed that ORAI1 increased CRAC currents if expressed with the CRAC activator STIM1. STIM1 has been previously shown to mediate CRAC activation after Ca 2+ store depletion [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%